Development of the cancer-patient social support questionnaire: reliability and validity - Sanna, Katarzyna; Cierpiałkowska, Lidia; Kleka, Paweł; Stelmach-Mardas, Marta; Iżycki, Dariusz (VIA Medica, 2019)
Background: Social support is an important mediator between disease and psychological adjustment both for the patient and the family members. The aim of this paper is to describe the development and initial reliability and validity of the Patient-Caregiver Social Support Questionnaire (KWPO), a four versions self report questionnaire to measure received and expected social support in cancer patients and given and demanded social support in informal caregivers. Methods: A total of 102 cancer-caregiver dyads completed the Patient-Caregiver Social Support Questionnaire together with other questionnaires as part of a larger study that aims to assess the health status of cancer caregivers in Poland. The reliability and validity of the questionnaire were analyzed. Results: Reliability of the KWPO can be considered satisfactory with a Cronbach’s alpha ranging from 0,89 for demanded social support to 0,923 for expected social support. Analysis of content validity showed CVR value, from 0.85 for expected social support to 0.92 for demanded social support. The principal dimension of the scales' versions were analyzed using confirmatory factor analysis (CFA). A four-factor model was supported by the data. The multidimensional aspect of the construct of social support was supported. Conclusions: The Patient-Caregiver Social Support Questionnaire can be considered suitable for measuring social support in cancer-caregivers dyads. It can be used to help Healthcare specialist to assess the patient's need for social support and caregivers competences to provide it. The questionnaire can help in determining the differences in provision and reception o social support and basing on results implement interventions.
Opracowanie oraz analiza trafności i rzetelności Kwestionariusza Wsparcia Społecznego Pacjent-Opiekun
Keywords: social support questionnire; alidation; cancer patients; family caregivers